TRADITIONAL AND NON-TRADITIONAL METHODS FOR DETERMINING THE TYPE OF SINGING VOICE - Василенко, Л. М. (SWorldJournal, 2022)
The article analyzes the methods of traditional and non-traditional nature of determining the type of singing voice in students in the process of vocal development. The peculiarities of these methods from the standpoint of their classification - by: range